Unpacking the Socio-Political Background of the Evolution of Boko Haram in Northern Nigeria: A Social Movement Theory Approach - Kingsley E. Amaechi; Rendani Tshifhumulo (Journal for the Study of Religion)
In the last decade, Boko Haram (BH) has become notorious across the world, because of its militancy and ultra-fundamentalist activities. Its violent activities have in many ways surpassed other similar African Salafi-oriented organizations, such as the AQIM in Algeria and al-Shabaab in Somalia. This article traces the socio-political and organizational background upon which this organization evolved in Northern Nigeria. Drawing from the social movement theory, it harnesses data,collected mostly from semi-structured interviews on some Salafi leaders, security personnel, politicians, and ordinary civilians who worked in the area. The study explains how the evolution of such an organization is rooted in context-specific political structures within Northern Nigeria. The argument is that these are enabling mobilization resources and political opportunities upon which initial BH activists established the organization in the region.